Perceived xerostomia, stress and periodontal status impact on elderly oral health-related quality of life: findings from a cross-sectional survey - Botelho, João; Machado, Vanessa; Proença, Luís; Oliveira, Maria João; Cavacas, Maria Alzira; Amaro, Luís; Águas, Artur; Mendes, José João (Springer Nature, 2020)
Background: To investigate if self-perceived xerostomia and stress are significant variables on the Oral-Health Related Quality of Life (OHRQoL) of elderly patients, considering the periodontal status, oral hygiene habits and sociodemographic characteristics simultaneously. Methods: The study cohort included 592 participants (320 females/272 Males), aged 65 years or older, representing the elder inhabitants of the Study of Periodontal Health in Almada-Seixal (SoPHiAS). Patients answered a socio-demographic and oral hygiene habits questionnaire. The Oral Health Impact Profile-14 (OHIP-14), Summated Xerostomia Inventory-5 (SXI-5) and Perceived Stress Scale-10 (PSS-10) were used. Full-mouth circumferential periodontal inspection was carried out. Multivariable regression analyses were used considering the level of periodontitis, clinical characteristics, the number of teeth, SXI, PSS-10, age, gender and oral hygiene habits. Results: Self-perceived xerostomia and stress showed a positive significant correlation with OHRQoL and each of its domains. Multiple linear regression analysis demonstrated the significant impact of SXI-5 (B = 1.20, p <  0.001) and PSS-10 (B = 0.35, p <  0.001) on the OHRQoL. SXI-5 (Odds Ratio (OR) = 1.28, p <  0.001) and PSS-10 (OR = 1.03, p = 0.022) were associated with a more frequently affected OHRQoL. The number of missing teeth, being male, mean probing depth and mean clinical attachment loss were also significant towards a frequently affected OHRQoL. Conversely, age was negatively associated with a lower OHRQoL. Conclusion: Self-perceived xerostomia and stress are significant variables towards OHRQoL in elderly patients. Future studies should consider these self-perceived xerostomia and stress when investigating the impact of periodontitis and missing teeth on quality of life of older adults.
Keywords: Xerostomia; Stress; Elders; Oral health-related quality of life; Periodontitis; Tooth loss; Aging